PENGARUH KOMPETENSI DAN STRES KERJA TERHADAP TURNOVER INTENTION PADA KARYAWAN FURAMAXCLUSIVE OCEAN BEACH SEMINYAK HOTEL - Ari Novarini; Ni Luh Putu Andriani; I Wayan Sujana; Made Ika Prastyadewi (JUIMA : JURNAL ILMU MANAJEMEN, 2022)
Human resources are very important in every organization, the goals and objectives that have been set will not be achieved if human resources cannot make a major contribution to the successful achievement and goals of the company. The purpose of this study was to examine the effects of career development and work pressure on goal turnover. This research was conducted at FuramaXclusive Ocean Beach Seminyak Hotel. The number of respondents is 80 people. Collecting data by distributing questionnaires using a Likert Scale. Data analysis techniques are several linear regression analysis techniques using SPSS version 21. Based on the results of linear regression analysis obtained a negative and significant career development effect on turnover intention, job stress has a positive and significant effect on turnover intention.